1992
DOI: 10.1007/bf00014247
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of suspension feeding anuran larvae to different particle sizes at low concentrations (Amphibia)

Abstract: The influence of particle size, initial particle concentration and larval stage on the ingestion rate, `retention efficiency', and filtering rate of anuran larvae with varying filter apparatus anatomy and different life histories was investigated for four species . Larvae of premetamorphic Stages 28 and 32 and prometamorphic Stage 40 were selected for filtering experiments on the basis of their different growth rates . Three different sizes of silica gel particles were offered as mock food . Particle concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
(70 reference statements)
1
23
1
Order By: Relevance
“…Since both the distance between the upper jaw articulations (SRA; a measure of gape width) and the distance between the ceratohyal articulations (CAW; a measure of buccal cavity width) scale with negative allometry in all species, which together would seemingly diminish filter feeding capabilities through ontogeny, allometric or proportional enlargement of the jaw closing muscles suggests increasing importance of rasping feeding as these animals grow. This observation is supported by experimental data indicating decreasing efficiency of filter feeding at later stages during larval ontogeny in anurans (Viertel, 1990(Viertel, , 1992.…”
Section: Patterns Of Chondrocranial Allometrysupporting
confidence: 75%
“…Since both the distance between the upper jaw articulations (SRA; a measure of gape width) and the distance between the ceratohyal articulations (CAW; a measure of buccal cavity width) scale with negative allometry in all species, which together would seemingly diminish filter feeding capabilities through ontogeny, allometric or proportional enlargement of the jaw closing muscles suggests increasing importance of rasping feeding as these animals grow. This observation is supported by experimental data indicating decreasing efficiency of filter feeding at later stages during larval ontogeny in anurans (Viertel, 1990(Viertel, , 1992.…”
Section: Patterns Of Chondrocranial Allometrysupporting
confidence: 75%
“…In contrary, the body surface of anuran larvae including their large tail fins play a role in gas exchange (Boutilier et al 1992;Ultsch et al 1999). Additionally high amounts of water are in close contact with the epithelia of the oral cavity, the filter apparatus and the gills during ventilation (Gradwell 1972a(Gradwell , b, c, 1975Hoff, 1979, 1982;Viertel 1990Viertel , 1992. It has to be suggested that anuran larvae are much more exposed to their aquatic environment and as Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The larvae are obligate suspension feeders pumping high amounts of water through their buccopharynx with the suggested consequence of tremendously increased contact to the compounds (Viertel 1990(Viertel , 1992. Reproduction was initiated by injection of human chorionic gonadotropin into the dorsal lymph sac of X. laevis.…”
Section: Methodsmentioning
confidence: 99%
“…Hall and Larsen (1998), among other observations on the ontogeny of the chondrocranium of Spea intermontanus, indicated that the area of the muscular process of the palatoquadrate also scales with negative allometry. Since the muscular process serves as the insertion site for the orbitohyoideus muscle, which is the major depressor of the buccal pump, these observations taken together may provide some morphological evidence for the decreasing efficiency of filter feeding associated with ontogeny observed by other researchers (Gradwell, 1968(Gradwell, , 1972Wassersug, 1972;Viertel, 1990Viertel, , 1992. Unfortunately, most studies of larval anuran feeding mechanics and efficiency have focused on the buccal pump and comparable studies regarding scaling of components of the tadpole jaw apparatus are lacking.…”
mentioning
confidence: 87%